Governance apathy and Social Hazards: A Case Study of Child Labour in Handloom Industry: INTRODUCTION , The possibility in this study, Defining Child Labour, Reasons for sustaining child labour, Sketching Child Labour in World Map, Indian Scenario, Who are the Child Labourers?, Indian Legislation for children from exploitation in Child labour, The Policy Framework for Child Labour, Concluding words - Afroz, Dr Md; Ziyauddin, K M (IJRDO - Journal of Social Science and Humanities Research, 2019)
India is currently witnessing large number of child labour, unfortunately nothing concrete has been done except legal conventions. It continues to be one of the major social issues confronting India with more than 100 million children engaged in various activities. On the part of governance of governments has been moreover filled with apathy. The policy lapses surmounting social hazards consequently large number of our future generation would be lost without making any contributions to the state’s development rather they will be lost nowhere. Due to various research and documentation on the scale and intensity of the problem and particularly commendable work of NGOs, research institutions and academia to an extent, the issue has been on and off in the public domain and kept alive in the minds of the civilized society. The deep rooted structure of Indian society has perpetuated the continuity of child labour and huge of them into hazardous industry. The capitalist system of production provided best avenues to the labour but suited to the industry aimed at surplus and more surpluses. The Nobel Prize given to person worked towards the elimination of child labour is a witness the cruel reality to the rich and unequal society. The hazards to the innocent life of children are one of the fundamental crimes against humanity but in reality it exists in all forms. This paper derives the research base of in the handloom industry in India and how the government’s apathy has deepened the magnitude of the child labour. The present study is primarily based on a study conducted on the larger issue of child labour in handloom sector in the state of Uttar Pradesh. My understanding does count the major role of certain factors for the continuous existence of this cruel reality. The seriousness of the responsible factor remains to be poverty for its high incidence, prevalence and perpetuation of child labour. So the same reason remains with handloom industry in India. It tries to bring the myriad form of problems associated for the existence of child labour and how the children at a very tender age gets deprived from the basic human rights. This also raises the fundamental questions of preventing the soft population entering into the unending tyranny of exploitation and deprivation and continues to live in the process of exclusion.